CHANGES IN THE INTENSITY OF UTERINE CIRCULATION IN PREGNANT WOMEN WITH A HISTORY OF CHRONIC ENDOMETRITIS - В. Ліхачов; О. Тарановська (Bukovynian State Medical University, 2023)
Introduction. An essential prerequisite for the normal course of pregnancy is a complete gestational remodeling of the blood circulation, when the spiral arteries are transformed into uteroplacental vessels with reduced resistance and constant blood flow. Chronic endometritis is characterized by morphofunctional changes in the mucous membrane and microcirculatory disorders in the pool of spiral arteries. If pregnancy develops with the above disease, it may lead to disruption of gestational remodeling of the spiral arteries and contribute to increased resistance to fetoplacental blood flow. Aim. To study the peculiarities of blood flow in the uterine spiral arteries and uterine arteries during pregnancy in women with a history of chronic endometritis and to evaluate the role of preconception care in the prevention of pregnancy complications. Material and Methods. 303 women with chronic endometritis were followed during pregnancy. Of these, 135 received antepartum treatment (Group I), which included broad-spectrum antibiotics, hormone replacement therapy for 3 months, and L-arginine during the antepartum period and the first 17-18 weeks of pregnancy. The other 168 women received no treatment during the preconception period (Group II). A control group of 20 healthy patients without chronic pre-pregnancy endometritis was also included. Doppler ultrasound of the spiral and uterine arteries was performed at 5-6 weeks of gestation and 17-18 weeks of gestation. The systolic-to-diastolic ratio (SDR) was calculated as the ratio of the maximum systolic blood flow velocity to the end-diastolic velocity, the pulsatility index (PI) was calculated as the ratio of the difference between the maximum systolic and minimum diastolic velocities to the mean blood flow velocity, and the resistance index (RI) was calculated as the ratio of the difference between the maximum systolic and minimum diastolic velocities to the maximum systolic blood flow velocity. The obtained data were processed using the methods of mathematical statistics, calculating the mean sample values (M), variance (σ), standard error of the mean (m), applying the Student's t-test and calculating the odds ratio using the statistical software "STATISTICA" (StatSoft Inc., USA). During the research, the principles of patient-centered care were followed in accordance with the requirements of the Tokyo Declaration of the World Medical Association, the International Recommendations of the Helsinki Declaration on Human Rights, the Convention on Human Rights and Biomedicine of the Council of Europe, the Laws of Ukraine, the Orders of the Ministry of Health of Ukraine, and the requirements of the Ethical Code of the Ukrainian physician. The paper is an excerpt from the initiative scientific research project of the Department of Obstetrics and Gynecology No. 2 at Poltava State Medical University, entitled "Optimization of approaches to the management of pregnancy in women at high risk of obstetric and perinatal pathology" (State registration number 0122U201228, duration:10.2022-09.2027). Results. In healthy women at 5-6 weeks of gestation, low resistance blood flow with low pulsatility and high diastolic component was observed in the uterine spiral arteries, as indicated by relatively low resistance indices. In Group II patients who became pregnant with chronic endometritis, an increase in SDR by 11.3% (p<0.01), PI by 36% (p<0.01) and RI by 36.2% (p<0.05) was observed in the spiral arteries at 5-6 weeks of pregnancy, as well as at 17-18 weeks, when SDR increased by 23% (p<0.001), PI by 63% (p<0.001) and RI by 47.5% (p<0.01) compared to healthy women. No significant changes in resistance indices were found in the uterine arteries. The calculated blood flow indices in the uterine spiral arteries at 5-6 weeks of gestation were significantly higher in those Group II women who developed pre-eclampsia later in pregnancy. In these patients, SDR, PI, and RI were 12.4% (p<0.05), 21.7% (p<0.05), and 17.7% (p<0.05) higher, respectively, than in group II women who did not develop pre-eclampsia during pregnancy. Furthermore, the more significant the increase in vascular resistance at the beginning of pregnancy, the more severe the pre-eclampsia. At 17-18 weeks' gestation, the increase in Doppler blood flow indices in the uterine spiral arteries was more pronounced and was accompanied by an increase in SDR, PI, and RI in the uterine arteries. In women of Group I who received pre-pregnancy treatment for chronic endometritis, both at 5-6 weeks and at 17-18 weeks of pregnancy, the values of resistance indices in the uterine spiral arteries were significantly lower than in the group of patients who did not receive such treatment. A more favorable course of pregnancy was also observed: the incidence of spontaneous abortion decreased by a factor of 2.3 (OR 5.20; 95% CI [1.75-15.42]; p <0.05), and the incidence of pre-eclampsia decreased by a factor of 1.8 (OR 2.3; 95% CI [1.25-4.31]; p <0.05). At the same time, the proportion of moderate forms of pre-eclampsia increased (85% of cases of moderate pre-eclampsia in Group I versus 73% in Group II) and the proportion of severe forms decreased (15% versus 27%). The mean duration of disease manifestation also decreased (34.3±0.4 weeks in Group I versus 29.4±0.6 weeks in Group II). Conclusions: In patients with chronic endometritis, pregnancy is associated with a high incidence of spontaneous abortion, especially in early pregnancy, and pre-eclampsia. This is accompanied by vasoconstriction and spasm of the uterine spiral arteries, as evidenced by a significant increase in the resistance indices of these vessels, which appears as early as 5-6 weeks of pregnancy and progresses to 17-18 weeks. It is more pronounced in women whose pregnancy is complicated by the development of pre-eclampsia. Preconception treatment of chronic endometritis can reduce vascular resistance in the pre-placental circulation at the stage of cytotrophoblastic transformation of the walls of the spiral arteries, which leads to a decrease in the incidence of spontaneous abortion and preeclampsia, especially its severe forms.